2012
DOI: 10.1155/2012/917247
|View full text |Cite
|
Sign up to set email alerts
|

Using Wavelets to Understand the Relationship between Mortgages and Gross Domestic Product in Spain

Abstract: We use wavelet multiresolution decomposition and cross-wavelet analysis to reveal certain properties in financial data related to mortgages to households and gross domestic product data in Spain. Wavelet techniques possess many desirable properties, some of which are useful as a vehicle for analysing economic and financial data. In our case, wavelets are useful for drawing conclusions both in the time and frequency domains and for obtaining information on the different phases through which the study variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This strong volatility resulted from the port development process, owing to the influences of many uncertain factors. The periodicity of the high-energy regions was due to seasonal demand, represented by the high-frequency component ( d 1 and d 2 ) (González-Concepción et al 2012 ).
Fig.
…”
Section: Data Analytics For Port Throughputmentioning
confidence: 99%
“…This strong volatility resulted from the port development process, owing to the influences of many uncertain factors. The periodicity of the high-energy regions was due to seasonal demand, represented by the high-frequency component ( d 1 and d 2 ) (González-Concepción et al 2012 ).
Fig.
…”
Section: Data Analytics For Port Throughputmentioning
confidence: 99%
“…𝜔 0 is the mother wavelet's central frequency (the frequency at the centre of a Gaussian envelope) and To implement the CWT for this study, the Morlet wavelet is adopted because of its ability to be decomposed into both real and imaginary parts which allows for broader analysis of the dynamic movements between two signals or time series (Ferrer et al, 2018). Equally, an appropriate value of 𝜔 0 = 6 is employed as it provides a good balance between frequency and time localization, while simplifying interpretation given that the wavelet scale and frequency are inversely related (see Grinsted et al, 2004;Aguiar-Conraria et al, 2008;González-Concepción, Gil-Fariña & Pestano-Gabino, 2012;Aloui & Hkiri, 2014 for more detail). Subsequently, the Morlet wavelet used within this study is a truncated version expressed below.…”
Section: Continuous Wavelet-transform (Cwt)mentioning
confidence: 99%
“…Other researchers focused more on the operational differences between Islamic banking and conventional banks, as a cause of higher credit risk. They concluded that Islamic banks faced higher risks than conventional banks due to conflicts between their applied methods of handling credit risk and rules of Sharia (Elgari 2003;Ferhi 2018) There is a limited possibility for managing credit risk in Islamic banks, due to how Islamic rules relate to financial transactions. For instance, the use of haram goods, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%